New insights into “dead lithium” during stripping in lithium metal batteries - Chen, Xiao-Ru; Yan, Chong; Ding, Jun-Fan; Peng, Hong-Jie; Zhang, Qiang (Journal of energy chemistry, 2021)
The formation of dead Lithium during stripping process is investigated in the whole course from the electron transfer, the conversion of Li0 to Li+ and the diffusion of Li+. [Display omitted] Lithium (Li) metal attributes to the promising anode but endures the low Columbic efficiency (CE) and safety issues from the inactive Li accumulation. The metallic Li which is isolated from the lithium anode (named dead Li0) consists the major component of the inactive Li. We systematically and meticulously investigated the formation and evaluation of dead Li0 during stripping process from electron transfer, the oxidation of Li0 to Li+ and the diffusion of Li+ through solid electrolyte interphase (SEI). The above-mentioned processes were regulated by adjusting the contact sites of electron channels, the dynamic rate of conversion from Li0 to Li+, and the structure as well as components of SEI. The design principles for achieving less dead Li0 and higher CE are proposed as a proof of concept in lithium metal batteries. This new insight sheds a comprehensive light on dead Li0 formation and guides the next-generation safe batteries for future application.